Classification of Network Traffic Based on Zero-Length Packets: A Review - Kalpana, S; Trivedi, T. Raghu (International Journal of Computer Sciences and Engineering, 2025)
Network traffic visitor’s classification is fundamental to network management and its performance. However, traditional traffic classifications, which were designed to work on a devoted hardware at very high line rates, may not feature well in digital software-primarily based surroundings. The advised fingerprinting scheme is strong to community conditions which include congestion, fragmentation, put off, retransmissions, duplications, and losses and to various processing abilities. Hence, its overall performance is largely independent of placement and migration problems, and consequently yields an appealing answer for virtualized software program-primarily based environments. We recommend an identical fingerprinting scheme for consumer datagram protocol traffic, which advantages from the equal blessings as the TCP one and attains very excessive accuracy as properly. Results show that our scheme effectively labeled about 97% of the flows on the dataset examined, even on encrypted facts.